IMPLEMENTASI KEBIJAKAN TATA RUANG SEMPADAN PANTAI CITEPUS PALABUHANRATU KABUPATEN SUKABUMI - Herri Azhari (STISIP Widyapuri Mandiri, 2022)
This research is motivated by the assumption that the implementation of the Citepus Palabuhanratu Beach border spatial policy has not run optimally. The purpose of this study is to find out (1) the implementation of the Citepus Palabuhanratu Beach border spatial policy, (2) to find out the supporting and inhibiting factors for the implementation of the Citepus Palabuhanratu Beach border spatial policy, and (3) what efforts are being made to overcome this problem. obstacles to the implementation of the Citepus Palabuhanratu Beach border spatial policy implementation. This study uses a qualitative approach. The informants of this study were the Head of Palabuhanratu Subdistrict, the Head of Citepus Village, the Secretary of Citepus Village, Members of the PP Satpol, Warung Owners, and tourists. The results of the research include (1) the implementation of the Citepus Palabuhanratu Beach border spatial policy has been running quite well, (2) There are several obstacles in the implementation of the Citepus Palabuhanratu Beach border spatial policy, and (3) the Sukabumi Regency Government has tried to overcome obstacles in implementation. coastal border spatial policy in improving the safety of tourists at Citepus Palabuhanratu Beach.